ANALISIS YURIDIS PEMBATALAN PERKAWINAN SEJENIS YANG TERJADI AKIBAT PEMALSUAN IDENTITAS (Studi Kasus Putusan Nomor 540/Pdt.G/2020/PA.GM.) - Amel Wahidliradefi; Anggun Lestari Suryamizon; Mahlil Adriaman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Same-sex marriages are marriages performed by same-sex couples who are commonly referred to as gay or lesbian, at the present time this type of marriage is rife, one of which occurred in Gelogor Village, Kediri District, West Lombok Regency, where the practice of marriage in Decision Number 540/Pdt.G/2020/PA.GM. This research will discuss the legal provisions against same-sex marriage due to identity falsification according to the provisions of Law Number 1 of 1974 concerning Marriage and its legal consequences. This research includes normative juridical research using a library approach, as well as using two sources of primary and secondary law. The results of this study indicate that the marriages carried out by Respondents I and II were invalid according to the terms and conditions of the marriage and an annulment of the marriage had to be carried out, moreover the falsification of identities committed by the Respondents had a significant impact on assets and third parties related to this practice. In addition, according to the Criminal Code in article 263 identity forgery, especially sex in marriage can be criminally charged because of indications of falsification of data and documents.